Selecting Graduate Supervisors in Islamic Higher Education: Bridging Educational Theory, Ethics, and Multicultural Practice - Awad Mabrouk (Solo Universal Journal of Islamic Education and Multiculturalism, 2025)
Objective: This study aims to investigate the process of selecting supervisors for master's and doctoral theses as a cornerstone of graduate program success. It specifically seeks to identify the gap between theoretical academic regulations and actual field practices in Arab universities compared to international standards. Theoretical framework: The research is grounded in the "Academic Quality Assurance" framework and "Institutional Theory," focusing on how formal selection criteria influence the quality of research outputs and the professional development of graduate students. Literature review: Previous studies emphasize that while selection criteria are theoretically established, their practical application remains inconsistent across different global academic systems, particularly highlighting the disparity between Arab and European institutional norms regarding supervisor accountability and student support. Methods: The study employs a comparative analytical approach, juxtaposing the supervisory selection mechanisms of Arab universities with those of European and international systems to highlight strengths, weaknesses, and procedural variances. Results: The findings reveal a significant "implementation gap" where formal methodologies are often bypassed by informal practices. The results also indicate that current selection processes in many Arab contexts lack rigorous monitoring and periodic evaluation of supervisor performance compared to international benchmarks. Implications: This research recommends the establishment of specialized "Supervisory Selection Committees" and the implementation of digital tracking systems to monitor supervisory loads and student progress, ensuring alignment with international quality standards. Novelty: The study provides an original comparative framework that bridges the gap between theoretical regulations and practical field realities in the Arab world, offering a roadmap for transitioning from administrative selection to a merit-based, quality-driven supervisory model.